Komparasi Tingkat Kesehatan Perbankan Syariah PT Bank Muamalat Indonesia dan PT Bank Mega Syariah Periode Maret 2005 - desember 2009 - Unggul Priyadi; Claresta Araminta (Jurnal Aplikasi Bisnis, 2017)
This research intend to analyze the factors affecting the health perfomance of syari'ah banking especially Bank Muamalat Indonesia (BMI) and Bank Mega Sjariah (BMS) in Indonesia. This study applied CAMEL Modified method that used  their finance report period March 200S—December 2009.This study concluded that BMS is better than BMI. BMS acquires healthy banks, criteria based on components and BOPO CAR, while BMI has a healtly bank criteria in terms of CAR, ROA. Both ofthe Islamic bank, BMI and BMS have an unhealthy bank category on aspects of BDR, LDR. If the BDR(Bad Debt Ratio) is low it will automatically make the entire results ofthe CAMEL Modified value has decreased.This led to declining financial performance and made the bank getting a bad predicate. Based on the conclusions above, BMI and the BMS are expected able to determine the effect of profits sharing that comes from thesefinancial statements as a whole.